A case study of diverse multimodal influences on music improvisation using visual methodology. (August 2016) - Tomlinson, Michelle M.
This case study employed multimodal methods and visual analysis to explore how a young multilingual student used music improvisation to form a speech rap. This student, recently arrived in Australia from Ethiopia, created piano music that was central to his music identity and that simultaneously, through dialogue with his mother, enhanced his linguistic skills. He selected and redesigned communicative modes across principal modes (learning domains). Through analysis of this student's redesign of a speech rap during his music improvisation at the piano, it was demonstrated that he promoted cognition and higher thinking. Conclusions showed he made a shift in understanding or meaning, empowering relations with his parents through a heightened understanding of music modes as the elements of music. The study revealed that modes encompassed all the senses (visual, aural, gestural and proxemics) in music improvisation while enhancing his verbal linguistic skills. By triangulating interviews and observations with video analysis, this study established that modes are not just unchangeable tools, but a means of situated social positioning and identity formation, and therefore resources for learning. It established that prior multicultural music learning was crucial to assist students' music improvisation to enhance communication across borders in local and global information societies.